Renormalization of general Effective Field Theories: formalism and renormalization of bosonic operators - Renato M. Fonseca; Pablo Olgoso; José Santiago (Journal of High Energy Physics)
Abstract We describe the most general local, Lorentz-invariant, effective field theory of scalars, fermions and gauge bosons up to mass dimension 6. We first obtain both a Green and a physical basis for such an effective theory, together with the on-shell reduction of the former to the latter. We then proceed to compute the renormalization group equations for the bosonic operators of this general effective theory at one-loop order.